2018
DOI: 10.4085/1062-6050-342-17
|View full text |Cite
|
Sign up to set email alerts
|

Taping to Improve Scapular Dyskinesis, Scapular Upward Rotation, and Pectoralis Minor Length in Overhead Athletes

Abstract: Context Deviations in scapular motions and subsequent alterations in associated soft tissues are thought to contribute to overuse shoulder injuries in overhead athletes. Whereas rigid and Kinesio taping are recommended for preventing these injuries, high-level evidence from clinical trials is still needed. Objective To determine and compare the short-term effects of rigid and Kinesio taping on scapular dyskinesis, scapular up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
9
1
3
Order By: Relevance
“…Although the study design allows for controlling non-specific effects of the intervention, adding a control group just applying Kinesio tape may be useful to control non-specific Kinesio tape effects. Fourth, although previous similar studies did not observe any considerable effect of placebo Kinesio tape, 11,33 we believe that the results of our study would be more reliable if we had another group that received a placebo Kinesio tape and we could observe how the placebo Kinesio tape can change the measured outcomes. Finally, it was not clear if patients' precision about pain and disability scores was affected by the length of time of Kinesio tape application and hands-on interaction in therapeutic exercise with the Kinesio tape group.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Although the study design allows for controlling non-specific effects of the intervention, adding a control group just applying Kinesio tape may be useful to control non-specific Kinesio tape effects. Fourth, although previous similar studies did not observe any considerable effect of placebo Kinesio tape, 11,33 we believe that the results of our study would be more reliable if we had another group that received a placebo Kinesio tape and we could observe how the placebo Kinesio tape can change the measured outcomes. Finally, it was not clear if patients' precision about pain and disability scores was affected by the length of time of Kinesio tape application and hands-on interaction in therapeutic exercise with the Kinesio tape group.…”
Section: Discussionmentioning
confidence: 46%
“…Kinesio tape was applied based on the study of Ozer et al 11 The taping technique was to improve shoulder and scapular biomechanics during exercises. In the first session, the physical therapist explained the details about Kinesio tape (e.g., history, materials, different colors, and different usage based on the techniques) for patients in therapeutic exercise with Kinesio tape group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study involving scapula correction in female handball players, kinesiology tape was applied by being stretched from the coracoid process past the upper trapezius to the lower trapezius, leading to improvement in the posterior tilt and upward rotation of the scapula through the mechanical effect of the kinesiology tape [37]. When kinesiology tape was stretched and applied to overhead athletes with scapular dyskinesis, mechanical correction of the abnormal scapular movement was observed [38]. Applying kinesiology tape to individuals with RSP showed that when the tape was stretched and applied to both shoulders while both scapulae were retracted, the shoulders of the individuals tried to return to the previous RSP but the kinesiology tape, due to its reduced elasticity, conferred resistance to RSP-thus creating an immediate correction effect [25].…”
Section: Relationship Between Kinesiology Taping and Rspmentioning
confidence: 99%
“…Hsu et al (23) reported that elastic taping, such as kinesiology taping, resulted in increased lower trapezius activity and positive scapular movement in baseball players with impingement syndrome. Ozer et al (24) reported that taping, regardless of the material, improved scapular dyskinesis and pectoralis minor length in overhead athletes. Although there has been much debate in the literature about whether or not taping is bene cial in patients and athletes with shoulder pain (25,26), many scholars and practitioners believe that it merely provides mechanical stabilization, rather than therapeutic e cacy (25).…”
Section: Introductionmentioning
confidence: 99%